2002
DOI: 10.1002/asi.10173
|View full text |Cite
|
Sign up to set email alerts
|

Browsing‐based conceptual information retrieval incorporating dictionary term relations, keyword association, and a user's interest

Abstract: A model of browsing-based conceptual information retrieval is proposed employing two different types of dictionaries, a global dictionary and a local dictionary. A global dictionary with the authorized terms is utilized to capture the commonly acknowledgeable conceptual relation between a query and a document by replacing their keywords with the dictionary terms. The documents are ranked by the conceptual closeness to a query, and are arranged in the form of a user's personal digital library, or pDL. In a pDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…users can either go to the results or can browse through related terms of the thesaurus displayed as suggested terms on the interface [21][22][23][24][25][26] . In second approach, in addition to what is achieved in the first approach, thesaurus terms are displayed on the interface along with a search window; users can either start retrieval process by clicking on thesaurus terms or they can enter a query in search window [15][16][17][18][19][27][28][29][30][31][32][33][34] . With respect to the implementation of thesaurus in enhanced browsing, it was found that a representation of thesaurus terms may be presented as hyperlinks or nodes on the interface 27,34 ; users can see the associated resources by clicking on a node.…”
Section: Include Excludementioning
confidence: 99%
See 1 more Smart Citation
“…users can either go to the results or can browse through related terms of the thesaurus displayed as suggested terms on the interface [21][22][23][24][25][26] . In second approach, in addition to what is achieved in the first approach, thesaurus terms are displayed on the interface along with a search window; users can either start retrieval process by clicking on thesaurus terms or they can enter a query in search window [15][16][17][18][19][27][28][29][30][31][32][33][34] . With respect to the implementation of thesaurus in enhanced browsing, it was found that a representation of thesaurus terms may be presented as hyperlinks or nodes on the interface 27,34 ; users can see the associated resources by clicking on a node.…”
Section: Include Excludementioning
confidence: 99%
“…gordon 28 developed a browsingbased photograph retrieval system where thesaurus terms are presented on the interface so that users can browse the collection. Nakashima 30 , et al used thesaurus for document arrangement to assist users by suggesting which documents are worth examining. Digital libraries may also provide its users an option to formulate queries by consulting thesaurus; and can also suggest alternatives from thesaurus if users do not use thesaurus in query formulation and if their search term do not match with thesaurus 25 .…”
Section: Thesaurus In Search Term Recommendationmentioning
confidence: 99%
“…It has a long tradition of widespread application in library and information science domains, particularly in Online Public Access Catalog (OPAC) systems. With the development of digital libraries and networked information systems in recent years, thesauri are drawing significant attention again for their values in retrieval aiding (Clark, Thompson, Holmback, & Duncan, 2000;Milstead, 1998), knowledge organization and management (NKOS, 2003) and conceptual retrieval (Clark et al, 2000;Nakashima, Sato, Qu, & Ito, 2003), and many pioneer works on concept space and ontology are derived from them as well (Chen, Ng, Martinez, & Schatz, 1997;Wielinga, Schreiber, Wielemaker, & Sandberg, 2001). In response to these trends, there is an increasing number of thesauri being incorporated into information retrieval (IR) systems and moved onto the Internet, such as the Humanities and Social Science Electronic Thesaurus (HASSET), Art & Architecture Thesaurus (AAT), and Unified Medical Language System (UMLS) (Shiri, 2000), a recommended standard for electronic thesauri is also introduced by the National Information Standard Organization (NISO; Milstead, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In some situations, users do not know what they really want to search for [11]. In other situations, they cannot specify precisely their information requirement [12]. However, most users can explain their requirements with reference to a specific example.…”
Section: Introductionmentioning
confidence: 99%